Monitoring physiological performance over 4 weeks moderate altitude training in elite Chinese cross-country skiers: an observational study - Yu, Y.; Wang, R.; Li, D.; Lu, Y. (International Journal of Environmental Research and Public Health, 2022)
The current observational study aimed to monitor the physiological performance over 4 weeks of living and training at a moderate altitude in elite Chinese cross-country skiers (8 males, mean age 20.83 ± 1.08 years). Lactate threshold, maximal oxygen uptake, blood, and body composition tests were performed at different time points to investigate the changes in physiological performance. The data were analysed by a one-way repeated measures ANOVA and a paired sample T-test between the test results. During the training camp, systematic load monitoring was carried out. Lactate threshold velocity, lactate threshold heart rate, and upper body muscle mass increased significantly (p < 0.01) after moderate altitude training. Maximum oxygen uptake was reduced compared to pre-tests (p < 0.05). Aerobic capacity parameters (maximal oxygen uptake, haemoglobin, red blood cell count) did not significantly increase after athletes returned to sea level (p > 0.05). These findings suggest that 4 weeks of moderate altitude training can significantly improve athletes` lactate threshold and upper body muscle mass; no significant improvement in other aerobic capacity was seen. Exposure time, training load, and nutritional strategies should be thoroughly planned for optimal training of skiers at moderate altitudes.